Analysis of volumetric data from the Coremas and Mãe D’água dams in Paraíba (Research, Society and Development, 2022)
The Paraíba State is inserted in a context of significant climatic variations, where in specific years, there is an abundance in the volume of water in the reservoirs. In others, the population suffers from the scarcity of this resource. In this sense, through the use of the technique of time series analysis, the present work analyzed the behavior of the volumetric level of the two main reservoirs of Paraíba, Coremas and Mãe D'água, located in the high backlands of Paraíba. The analyzed data were obtained from the Executive Agency for Water Management (AESA) site and the Climate Prediction Center (CPC) corresponding to monthly volumetric data from the dams as mentioned above and measurements of temperatures of anomalies in the ocean, respectively, from January 2013 to December 2021. For the analysis of the time series, the R 4.1.2 software was used, with the "forecast" package, making it possible to find and validate the best mathematical models to describe the behavior of the series of each weir, as well as make predictions for the possible behavior of the series until July 2022. From the results obtained, the best models for the historical series of the dams were ARIMA for the Coremas dam and ARIMA for the Mãe Dágua reservoir. In addition to these results, it was found that in times of El Niño, the water level in the dams was low, while in times of La Niña, an increase in the water level of the reservoirs was perceived.